Muscle α-adrenergic responsiveness during exercise and ATP-induced vasodilation in chronic obstructive pulmonary disease patients - Iepsen, U. W.; Munch, G. W.; Ryrsø, C. K.; Secher, N. H.; Lange, P.; Thaning, P.; Pedersen, B. K.; Mortensen, S. P. (American journal of physiology. Heart and circulatory physiology, 2018)
Sympathetic vasoconstriction is blunted in exercising muscle (functional sympatholysis) but becomes attenuated with age. We tested the hypothesis that functional sympatholysis is further impaired in chronic obstructive pulmonary disease (COPD) patients. We determined leg blood flow and calculated leg vascular conductance (LVC) during 1) femoral-arterial Tyramine infusion (evokes endogenous norepinephrine release, 1 µmol·min −1 ·kg leg mass −1 ), 2) one-legged knee extensor exercise with and without Tyramine infusion [10 W and 20% of maximal workload (WL max )], 3) ATP (0.05 µmol·min −1 ·kg leg mass −1 ) and Tyramine infusion, and 4) incremental ATP infusions (0.05, 0.3, and 3.0 µmol·min −1 ·kg leg mass −1 ). We included 10 patients with moderate to severe COPD and 8 age-matched healthy control subjects. Overall, leg blood flow and LVC were lower in COPD patients during exercise ( P < 0.05). Tyramine reduced LVC in both groups at 10-W exercise (COPD: −3 ± 1 ml·min −1 ·mmHg −1 and controls: −3 ± 1 ml·min −1 ·mmHg −1 , P < 0.05) and 20% WL max (COPD: −4 ± 1 ml·min −1 ·mmHg −1 and controls: −3 ± 1 ml·min −1 ·mmHg −1 , P < 0.05) with no difference between groups. Incremental ATP infusions induced dose-dependent vasodilation with no difference between groups, and, in addition, the vasoconstrictor response to Tyramine infused together with ATP was not different between groups (COPD: −0.03 ± 0.01 l·min −1 ·kg leg mass −1 vs. controls: −0.04 ± 0.01 l·min −1 ·kg leg mass −1 , P > 0.05). Compared with age-matched healthy control subjects, the vasodilatory response to ATP is intact in COPD patients and their ability to blunt sympathetic vasoconstriction (functional sympatholysis) as evaluated by intra-arterial Tyramine during exercise or ATP infusion is maintained. NEW & NOTEWORTHY The ability to blunt sympathetic vasoconstriction in exercising muscle and ATP-induced dilation in chronic obstructive pulmonary disease patients remains unexplored. Chronic obstructive pulmonary disease patients demonstrated similar sympathetic vasoconstriction in response to intra-arterial Tyramine during exercise and ATP-induced vasodilation compared with age-matched healthy control subjects.